Dynamics and challenges of technology transfer in Colombia: a systematic literature review - Valencia-Arias, Alejandro; Bonilla Restrepo, Karla Cristina; Villa-Enciso, Eliana; Valencia, Jackeline; Rua Hernandez, Juan Camilo; Ramírez-Ramírez, Diana Marleny (Frontiers in Research Metrics and Analytics, 2025)
IntroductionTechnology transfer in Colombia plays a critical role in promoting innovation and regional development. However, its implementation continues to face significant institutional, economic, and cultural challenges that hinder its effectiveness and sustainability.MethodsA systematic literature review was conducted in accordance with the PRISMA 2020 guidelines. The databases Scopus and Web of Science were used to identify peer-reviewed articles that addressed knowledge and technology transfer within the Colombian context.ResultsThe analysis revealed multiple barriers: institutional fragmentation, inadequate investment in R&D, lack of incentives for collaboration, and weak trust between academia and industry. Additionally, organizational rigidity and the limited adaptation of international transfer models to local contexts were identified as factors that reduce the effectiveness of these processes.DiscussionThe findings highlight the need to acknowledge regional particularities, foster inclusive governance, and promote horizontal relationships among stakeholders. Effective international strategies, such as open innovation, co-creation models, and hybrid technology transfer offices, could be adapted to the Colombian context. Strengthening institutional capacities, increasing R&D funding, and aligning innovation with social and environmental objectives are imperative to build a more robust and inclusive innovation ecosystem.